2002
DOI: 10.1038/sj.dmfr.4600704
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two compression algorithms and the detection of caries.

Abstract: At a compression ratio of 9:1, there were no significant differences among the original images, JPEG and wavelet compressed images for the detection of enamel caries. JPEG-compressed images performed inferiorly to the original and wavelet-compressed images for the detection of dentinal lesions. Wavelet compression is a better choice than JPEG at the compression ratio investigated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Janhom et al [2002] observed insignificant differences for JPEG-and JPEG2000-compressed radiographs compared to digitized 'originals'. Pabla et al [2003] also reported non-significant differences for JPEG compression levels between 1: 2.5-1: 16.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Janhom et al [2002] observed insignificant differences for JPEG-and JPEG2000-compressed radiographs compared to digitized 'originals'. Pabla et al [2003] also reported non-significant differences for JPEG compression levels between 1: 2.5-1: 16.…”
Section: Discussionmentioning
confidence: 75%
“…The majority of investigations into the detection of natural caries [Janhom et al, 1999[Janhom et al, , 2000Pabla et al, 2003;Wenzel et al, 1996] or artificial lesions [Koenig et al, 2004] on compressed radiographs are based on the wellestablished Joint Photographic Experts Group (JPEG) compression standard. We found only one paper [Janhom et al, 2002] using the more advanced wavelet compression technique detailed below.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wavelet-based coding has emerged as a state-of-the-art technology within the field of image compression and appears to be more robust than other compression techniques with respect to transmission and decoding errors as well as facilitates the progressive transmission of images. Different studies that have compared the DCT technique to wavelet transformation in different kinds of radiological images with different compression ratios provided contradictory results [18][19][20][21]. In immunohistochemical digital images, there is no agreement about whether JPEG2000 is better than JPEG or if differences are indistinguishable at lower or higher compression ratios with the two formats.…”
mentioning
confidence: 97%
“…For some time now, considerable effort has been made to evaluate digital image compression techniques to permit the image quality required for medical images [9][10][11][12][13][14][15][16][17][18][19][20]. These evaluations include subjective and objective metrics.…”
Section: Introductionmentioning
confidence: 99%